The Swedish NDC Scheme : Success on Track with Room for Reflection - Palmer, Edward; Könberg, Bo (World Bank, Washington, DC, 2019)
Sweden’s reform began with a published sketch in 1992 and developed into nonfinancial defined contribution (NDC) legislation in 1994. This paper discusses the underpinnings of the Swedish NDC scheme’s financial stability, factors influencing the adequacy of benefits, and its interplay with other components of the pension system: the public financial defined contribution scheme, the minimum pension guarantee, and the occupational schemes. The paper also includes information on the December 2017 broad six-party political agreement on forthcoming legislation. It concludes with recommendations for additional improvements in the overall old-age pension system, based on the analysis of financial stability, adequacy, and differences in outcomes, and the interaction of the NDC scheme with the guarantee benefits and the occupational schemes.